2009
DOI: 10.1002/mame.200800269
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Silver Nanoparticle Dispersions via a Dendritic‐Polymer Template Approach and their Use for Antibacterial Surface Treatment

Abstract: An easy and robust approach for the production of long‐term‐stable silver nanoparticle dispersions with narrow size distribution (mean diameter ≈3–5 nm) has been developed. Amphiphilic‐modified hyperbranched polyethyleneimines with core/shell architecture were used as macromolecular templates and carriers. We systematically investigated the antibacterial performance and morphology of thin silver‐loaded hyperbranched polymer coatings on poly(ethylene terephthalate) prepared by different wet coating techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Size and shape are important, with micro-scale particles ("bulk" equivalent) showing lesser effects than the NPs [4,[7][8][9][10][11]. The release of Ag ions from Ag NPs participates in their antimicrobial activity [12][13][14][15], thus extending the historical use of Ag ions as an antimicrobial agent. Ag NPs effect cell membranes [10], electron transport [16] and ATP-dependent transport mechanisms in bacterial cells [17].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Size and shape are important, with micro-scale particles ("bulk" equivalent) showing lesser effects than the NPs [4,[7][8][9][10][11]. The release of Ag ions from Ag NPs participates in their antimicrobial activity [12][13][14][15], thus extending the historical use of Ag ions as an antimicrobial agent. Ag NPs effect cell membranes [10], electron transport [16] and ATP-dependent transport mechanisms in bacterial cells [17].…”
Section: Introductionmentioning
confidence: 98%
“…Fast flow fractionation (FFF), a powerful tool for studying particle size in suspensions [4], and atomic force microscopy (AFM) for direct imaging, were used to determine size distribution of the Ag NPs and the particles in EPS. Increases in reactive oxygen species (ROS) is a proposed cause of Ag toxicity [10,13,[23][24][25][26][27]. Consequently, we examined the ability of Ag NPs to stimulate extra-and intra-cellular reactive oxygen species production in PcO6 cells.…”
Section: Introductionmentioning
confidence: 99%
“…There is enormous interest in the research of highly efficient and low-cost antibacterial surface treatments to avoid the breeding and spreading of the harmful microorganisms [4,5]. Most of the approaches for achieving antibacterial surfaces are based on silver particles [6][7][8][9]. The silver particles provide ions which are highly toxic to bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular architecture of the core/shell type hybrids used as hosts for silver nanoparticles can provide an improved control of the silver ion release and therefore an adjustment of the antibacterial affect specific to its application. This can be succeeded by the utility of the controllable generation structure of dendrimer nanoparticles (Gladitz et al, 2009). It has been shown that dendrimer films effectively inhibited the colonization of the Gramnegative bacteria Pseudomonas aeruginosa (strain PAO1) and, to a lesser extent, the Gram-positive bacteria Staphylococcus aureus (SA).…”
Section: Dendrimers As Antibacterial or Antimicrobial Agentsmentioning
confidence: 99%